Understanding supervision in health and social care through the experiences of practitioners in Scotland. Issue 2 (18th April 2017) - Allbutt, Helen; Colthart, Iain; El-Farargy, Nancy; Sturgeon, Caroline; Vallis, Jo; Lough, Murray
Abstract : Purpose: The purpose of this paper is to describe a collaborative study on supervision with health and social care practitioners in Scotland. The study attempted to gain a better understanding about the use and benefit of supervision from a multiprofessional perspective. Design/methodology/approach: Consultation events with health and social care staff and 12 informant interviews were undertaken. Data analysis was via the Framework Method. Findings: Managers were more likely to conceive of supervision as a positive intervention than those in lower pay bands. The practice of supervision was variable. Not all staff appeared to take part in regular supervisory activities even when it was mandated. A lack of professional, organisational or local commitment to implement robust supervisory structures and processes was seen as the major barrier to effective supervision. Research limitations/implications: This was a small study, thus findings would need to be confirmed by health and social care staff working across a wider spectrum of disciplines and regions across Scotland. Practical implications: A combination of factors would seem to determine effective supervisory practice. Supervision was perceived to be of benefit when individuals were willing to participate fully, when there was reflection and planned action, constructive challenge, respectful relationships, regular and protected sessions and processes were appropriate to an employee's circumstances. Originality/value: This study situates supervision in the current context of health and social care and finds it to be an irregular practice. The findings confirm the existing literature about the importance of supervisor-supervisee relationships but explain differing perceptions of supervision in terms of staff seniority.